Aplikasi E-Learning Agama Islam Berbasis Android Pada TKQ Husnul Khotimah - Maulana, Lukman (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2020)
The magnitude of influence of technological developments and information has penetrated in many aspects of human life, there is no educational world. By incorporating technology and information into the implementation of e-learning concept, an education system is ready to transform into a digital education because the concept is able to overcome the barriers of space and time because utilize network facilities via the internet which can be accessed anywhere and anytime. TKQ Husnul Khotimah in the learning process is still conventional, where the learning process is carried out with the requirements of meeting between students and teachers in the class. Developing Android-based e-learning apps is expected to improve learning quality.Keywords: Application, Android, Internet, E-Learning